Socio-emotionality: brief introductory considerations based on Vygotsky's Zone of Proximal Development (ZPD) (Research, Society and Development, 2025)
This essay aims to discuss and present the term "Socioemotionality." Anchored in the epistemology of Complexity, the concept presented here differs from socioemotional competencies, skills, and intelligence. Based on a theoretical literature review (2020 to 2025), surveys were conducted in journals, theses, and dissertations based on the concept. The results demonstrate the non-existence of the term "socioemotionality." Using Vygotsky's Zone of Proximal Development as a reference, a parallel is drawn with the concept, aiming to demonstrate that new socioemotional interactions are, in the current context, mediated by other actors such as institutions, technologies, and social networks, with repercussions on learning and knowledge. Finally, this essay presents, as a result of the analyses, the characterizing elements of socioemotionality, the new matrices of socioemotional interactions, and their repercussions on social coexistence.